I warned you and yo didn’t listen me: poverty and inequality in Uruguay: I warned you and you didn’t listen to me: poverty and inequality in times of pandemic in Uruguay - Baráibar Ribero, Ximena (Critical Proposals in Social Work, 2022)
In Uruguay, the COVID’s arrival coincides with the starting of a new government, after right parties made up a new coalition of right parties, which replaced Frente Amplio in power. A year later, this country reality is more serious in health and social terms. This articule focuses on analysing impacts, particulary the increase -very significant for this country- of poverty and inequality. This is done base on the analysis of secondary soucrces, including documents made by de ruling coalition, national and international investigations and statements by goverment authorities. The conclution is that the worsening ot living conditions of large sectores of the population, is a consequence with the world situation, but also with government’s responses. Its strong liberal ideology has tendend to transfer to people the responsibility health and social consequences, reducing state invervention. Despite, having the country an institucionalized transfer system, the central foucus has been on baskets food, with almost no support for popular pots. Althoug announced in several times, these responses have had little amount of money and duration and have been accompained with autoritiy’s speech of suspicion about the recipient populations. The bet is on economic growth -that must be promoted with state invertions reduced- and generating employment in that way. This is realized without any discuss about the existance of poor working people and the characteristics of jobs that allow to live out of poverty.